2012
DOI: 10.1002/wcc.193
|View full text |Cite
|
Sign up to set email alerts
|

Climate policy processes, local institutions, and adaptation actions: mechanisms of translation and influence

Abstract: This paper reviews and synthesizes the published literature on decentralization of renewable resources and development interventions to identify four key lessons for future adaptation planning at the national level. After presenting an analysis of why studies of decentralization reforms are relevant to adaptation planning, the paper examines priority adaptation projects identified by 47 Least Developed Countries in their National Adaptation Programmes of Action (NAPAs). Our research analyzes the range of insti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
58
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 59 publications
2
58
0
Order By: Relevance
“…NAPAs have led to the creation of 513 adaptation projects at a cost of $1.5 billion, which represents a relatively small amount on a global scale (UNFCCC, 2012). A recent study has shown that in many countries, the NAPAs have resulted in very few practical outcomes, but they are still in the early planning stages (Agarwal et al, 2012;Hillman et al, 2015).…”
Section: Background To the Problemmentioning
confidence: 99%
See 4 more Smart Citations
“…NAPAs have led to the creation of 513 adaptation projects at a cost of $1.5 billion, which represents a relatively small amount on a global scale (UNFCCC, 2012). A recent study has shown that in many countries, the NAPAs have resulted in very few practical outcomes, but they are still in the early planning stages (Agarwal et al, 2012;Hillman et al, 2015).…”
Section: Background To the Problemmentioning
confidence: 99%
“…As a result, the success for adaptation heavily depends on the efficiency in which decision making can be translated across multiple scales to contribute to effective local outcomes. In the case of NAPAs, few have examined how to coordinate adaptation efforts across different sectors and scales (national, regional, local), the institutional arrangements necessary to implement adaptation projects, and how to utilize resources and actors to implement adaptation priorities (Agarwal et al, 2012). These programs (and adaptation strategies in general) have found the multi-scalar and cross-sectoral nature of adaptation challenging and that more research could increase our understanding on how to make such programs more effective (Adger, 2016;Dzebo & Stripple, 2015).…”
Section: Background To the Problemmentioning
confidence: 99%
See 3 more Smart Citations